Determinants of Customers’ Satisfaction Towards Services Provided by Agencies in Urban Transformation Centre (UTC) - Rosli, Anita; Siong, Ting Ing (International Journal of Economics, Business and Management Studies, 2018)
The research was conducted to study determinants of customers’ satisfaction towards services provided by various agencies at UTC Sibu, Sarawak. This study applied the five dimension of service quality (tangibility, reliability, responsiveness, assurance, and empathy) by using the SERVEQUAL model developed by Parsuraman et al. (1988) to study about the customer satisfaction. A total of 380 respondents were selected through convenient sampling method, where the self-administered questionnaire was used to conduct the survey. The Pearson correlation analysis was used to identify the relationship of the factors with the customers’ satisfaction. The result showed that the average mean score for the customers’ satisfaction is 3.79 which indicates that the customers have a high level of satisfaction towards services provided by agencies in UTC Sibu, Sarawak. The factors of tangibility, reliability, and empathy were significantly influencing the level of customer’s satisfaction at 1%.